Investigação das propriedades físico-químicas das emulsões de óleo essencial da casca da canela (Cinnamomum cassia) - ARAÚJO, Cássio Fernandes de (2023)
Recently, there has been a significant increase in demand for nanomaterials due to the emergence of new challenges that conventional methods cannot solve. This increase in demand is mainly related to food degradation and the spread of resistant microorganisms, which has a significant financial impact on companies that produce consumer goods, indirectly affecting society in general. Large research centers are focused on finding effective materials that can overcome these difficulties without causing damage to the environment or health. In this context, emulsions have emerged as a promising solution to these problems. Therefore, the aim of this study is to investigate how storage time affects the physicochemical characteristics of emulsions obtained by the spontaneous emulsification method. These emulsions are produced using cinnamon bark essential oil (Cinnamomum cassia) at 6% and 3% (v/v), together with coconut oil as an Ostwald ripening inhibitor (MO) and Tween 80 as a surfactant. Visual, spectroscopic, pH and viscosity analyses were carried out to characterize the prepared samples.